SOSIALISASI KAPABILITAS FINANSIAL DAN TATA KELOLA KEUANGAN DALAM MEMPERSIAPKAN SISWA SMAN 1 MAJA MENJADI MAHASISWA BARU UNIVERSITAS PAMULANG KAMPUS SERANG PADA PROGRAM STUDI MANAJEMEN - Aura Nabilat En Najla; Mina Wati Dewi; Ani Apriani; Alfatha Abda; Rafi Fajar Rizki (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This socialization activity aims to implement community service through the enhancement of digital financial literacy among SMAN 1 Maja students, as preparation for becoming new students at Universitas Pamulang Serang in the Management Study Program. As young individuals, students play a crucial role in developing healthy financial management habits from an early age. However, there is still a lack of understanding regarding personal financial management and limited skills in utilizing digital technology to support financial decision-making. This program includes material presentations, interactive discussions, and simulations using digital financial applications to help students manage expenses and develop wiser consumption patterns. The results indicate an increased awareness of the importance of digital financial literacy and motivation among students to be more selective in financial management. Nevertheless, challenges such as limited experience in applying digital financial technology and strong social influence remain. Therefore, ongoing guidance is necessary to ensure that financial literacy is consistently applied. Through this socialization, students are expected to develop healthy, rational, and responsible consumption patterns in accordance with sound financial management principles, providing a solid foundation for their academic life at the university.